Organoids: life in three dimensions- a review - CNV, Akhila; Prakash A, Ravi; Kanth M, Rajini; G, Sreenath; K, Sowmya; B, Radhika (International Journal of Dental Research, 2019)
Most of the diseases in humans are as a result of complex interactions occurring at cellular and molecular level. Research today has been focused in an attempt to reveal precisely the cellular evolution into pathogenesis. There are vast array of research fields, which include molecular biology, imaging techniques, etc. One of such field recently advancing worldwide is â€œOrganotypingâ€. It is the successor of two dimensional cell cultures. Miniature organs and disease models can be produced from cells having the ability to proliferate and differentiate, by adopting definite protocols. Organoids are the potential tools to probe human biology and diseases; thereby they may change the approach to study diseases and provide treatment, in a more beneficiary way to the patient. Also organoids are used in vaccine production, cancer research, microbiology, tissue regeneration, drug testing, etc. Clinical trials are more devastating and may cost life of patients included in study. As such, organoids can be included in the protocols of clinical trials, through which the outcome of the study can be estimated. They open the doors for newer research methods and innovations, which are in peak requirement of present day scenario where new diseases are emerging and the diseases already existing are not yet cured.Â Â Â